IFRS and US GAAP : A Comprehensive Comparison - Shamrock, Steven E. (Hoboken, New Jersey John Wiley and Sons, 2012)
"International Financial Reporting Standards (IFRS) are used in over 120 countries. US companies will inevitably encounter IFRS when evaluating the financial health of suppliers and customers. IFRS and US GAAP: A Comprehensive Comparison provides instruction in accounting under IFRS within the context of US accounting standards. Practical and easy-to-use, this book includes a case study of a first time IFRS adoption, emphasizing the much greater degree of professional judgment that is needed for IFRS. This book: Provides a heavy emphasis on practical examples ; Includes an online companion website with downloadable spreadsheets and templates ; Reflects current financial reporting trends ; Addresses accounting requirements of which today's auditors, accountants and preparers of financial reports need to be aware. Clarifying IFRS, its impact on US companies, and where to start in understanding it, IFRS and US GAAP prepares US accountants to be knowledgeable with day to day financial accounting issues using IFRS's substantial similarity with US GAAP as a context."
Include Index
Keywords: United States -- Accounting--Law and legislation -- Accounting--Standards